New host records of parasitic isopods of Tropical Eastern Pacific marine fishes, with remarks on the taxonomy and distribution of the species - Mayra Ixchel Grano-Maldonado; Gerardo Pérez-Ponce de León; Hugo Aguirre-Villaseñor; José Salgado-Barragán (Nauplius, 2025)
Abstract Marine fishes harbor a wide array of metazoan parasites, including helminths and crustaceans such as copepods and isopods. Even though the coast of Sinaloa stands out in Mexico by the volume of captured marine fishes, information about the diversity of their parasites is still very scarce. Isopods belonging to the families Cymothoidae, Gnathiidae, Corallanidae, and Aegidae are composed of temporary or obligate ectoparasites of the skin, gills, gill-chamber, or mouth of marine fishes across the world. In this study, we report data on the presence of isopods of the families Cymothoidae, Gnathiidae, and Aegidae infecting fishes from three localities at Sinaloa, Mexico. Fishes were obtained from commercial capture and the body surface, gill chamber, and mouth were examined for parasitic isopods. We report five parasitic isopod taxa in 16 fish host species, including Ceratothoa gilberti (Richardson, 1904), Nerocila californica Schioedte and Meinert, 1881, a potential new species identified as Cymothoa sp. A, Rocinela signata Schioedte and Meinert, 1879, and praniza and zuphea larvae of Gnathiidae species. Also, we compiled information on previous records of these species in marine fishes along the Mexican Pacific coast and discussed the importance of our findings for understanding the diversity and distribution patterns of these ectoparasites in the Southeastern Gulf of California.